The influence of quality of work life (QWL) and organizational commitment on job performance among academics in the Malaysian public universities - Bahyah, Abdul Halim; Zainudin, Awang; Amauche, Ehido (2019)
In Malaysian, the education sector has become very significant in transforming Malaysia into a high-income country. Therefore, the emphasis on the higher institutions has increased while the jobs of academics have become increasingly demanding and challenging. The jobs of Malaysian academics are increasingly challenging because of the requirement of attaining the key performance indicators (KPI) and the constant demands from universities and from stakeholders to produce excellent and employable graduates in the country. Because of the aforementioned challenges in today’s workplace, high commitment is required from the public universities academics. Thus, it is important for employers to understand the quality of work life (QWL) of their employees if they are concerned about improving the employees’ organizational commitment and job performance. Accordingly, the purpose of this research is to close the gap that presently exists in the quality of work life (QWL) study by determining the factors that improve or impede the relationship between QWL and job performance (JP) with the mediating effect of organizational commitment (OC) among academics in the Malaysian public universities.